A Cross-disciplinary Study of Hedging Expressions in English Articles of Iranian Writers - Rezvani, Reza; Javadi, Mohammad (Widya Mandala Catholic University Surabaya, 2021)
Research on the use of hedging strategies as one of the key issues of rhetorical organization of academic texts has gained growing attention during the past few decades. The present study aimed to explore the frequency and form of hedging expressions in the abstracts of Iranian writers’ English research articles where findings and claims were more explicitly projected. To this end, a random sample of 200 abstracts (50 each) was drawn equally from the four subfields of chemistry and mathematics, and philosophy and English randomly selected from the two academic fields of Soft Sciences and Hard Sciences respectively as suggested in Biglan’s (1973) typology of academic disciplines. The tally and analysis of the tokens of the hedge expressions indicated that the abstracts from the soft sciences differed from those from the hard sciences in terms of both frequency and form. The results revealed that the writers from the soft sciences tended to employ more hedge expressions than hard sciences writers. More specifically, whereas soft sciences writers utilized more modals, verbs, nouns, adjectives, and adverbs, their counterparts opted for more conditional expressions. Moreover, epistemic and cognition verbs were found to be the most frequently used hedging expressions in both sciences. This study discusses the research and pedagogical implications of the findings in the context of Iranian academia.